(untitled) (Research, Society and Development, 2021)
Objective: This study aims to present how humanization from the offer and fabrication of a toy can change the daily life of the ward. Methodology: This is a descriptive study, with a qualitative approach. The research was developed in the wards, from reading the field diaries of the meetings held with 68 caregivers, in a group and individually, for the construction of playful material, rattle and EVA Identification Plate, which were part of recycled material. Results: As a result, we have the presentation of the proposal, the construction of the material, the guidelines and feedback from the participants. Discussion: From the intervention, the facilitator, the caregivers and the team reported how the ward became more humanized, changing the daily routine, facilitating the dialogue and reducing the stress of the caregiver and their child. Conclusion: It is concluded that more actions in the wards are necessary, once the acceptance of new techniques in these environments, greater well-being can be achieved for the caregiver and the child.